2021
DOI: 10.7717/peerj.11209
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri TSR332 and Lactobacillus fermentum TSF331 stabilize serum uric acid levels and prevent hyperuricemia in rats

Abstract: Background Uric acid (UA) is the end product of purine metabolism in the liver and is excreted by the kidneys. When purine metabolism is impaired, the serum UA level will be elevated (hyperuricemia) and eventually lead to gout. During evolution, humans and some primates have lost the gene encoding uricase, which is vital in UA metabolism. With the advances of human society, the prevalence of hyperuricemia has dramatically increased because of the refined food culture. Hyperuricemia can be contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 40 publications
0
30
1
1
Order By: Relevance
“…Kuo et al. reported that Lactobacillus reuteri TSR332 and Lactobacillus fermentum TSF331 stabilized serum UA levels and prevented HUA in rats ( 29 ). In addition, prophylactic treatment with Lactobacillus brevis DM9218-A decreased UA concentration in HUA rats ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuo et al. reported that Lactobacillus reuteri TSR332 and Lactobacillus fermentum TSF331 stabilized serum UA levels and prevented HUA in rats ( 29 ). In addition, prophylactic treatment with Lactobacillus brevis DM9218-A decreased UA concentration in HUA rats ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al found that Limosilactobacillus fermentum JL-3 reduced UA levels in mice and regulated the structure of gut microbial (19). Kuo et al reported that Lactobacillus reuteri TSR332 and Lactobacillus fermentum TSF331 stabilized serum UA levels and prevented HUA in rats (29). In addition, prophylactic treatment with Lactobacillus brevis DM9218-A decreased UA concentration in HUA rats (30).…”
Section: Discussionmentioning
confidence: 99%
“…Then, 20 μl mixed solution was extracted and analyzed by HPLC (Shimadzu, Tokyo, Japan) (Chromatographic column: ZORBAX Eclipse Plus C18, 4.6 × 250 mm, 5-Micron; UV detection wavelength: 254 nm; Mobile phase: 20 mmol/L isogradient phosphate-buffered solution; Flow rate: 1 ml/min; Elution time: 45 min; Column temperature: 25°C). Corresponding results were calculated by the following formula ( 20 ):…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, Lactobacillus is the main category of probiotic microorganisms that ameliorates hyperuricemia. Specifically, Lactobacillus plantarum , 22,23 Lactobacillus reuteri , 24 Lactobacillus fermentum , 25 Lactobacillus brevis 26 and Lactobacillus gasseri 27,28 are species that can reduce the levels of serum uric acid through different pathways. Probiotic strategies to ameliorate hyperuricemia aim to reduce UA biosynthesis and promote UA secretion.…”
Section: Introductionmentioning
confidence: 99%